Seawater Pollution Level and Biodiversity Diversity in Tarahan Island, Serang, Banten - Anita Fanoura; Najmi, Sabilla; Wahdaniyah Pratiwi; Faisal Akbar Munggaran; Muhamad Niam Bastomi; Moch Saad; Prakas Santoso; Afifah Nurazizatul Hanasah; Bagus Syahriil Fahlevi (Grouper, 2025)
Coastal ecosystems are transitional areas between land and sea with high biodiversity. However, currently coastal ecosystems are experiencing complex changes, many developments and activities in coastal areas cause indirect damage. One of the impacts is the entry of pollutants from land into the sea, such as heavy metals, pesticides and organic waste, which can disrupt the balance of marine biodiversity. This study aims to analyze the diversity of biodiversity and the level of seawater pollution in Tarahan Island, Serang, Banten. The method used was purposive sampling for water sampling, cryptic biota and seagrass. Biota identification was done visually using scientific references such as the World Register of Marine Species (WoRMS), while the level of water pollution was measured through Biochemical Oxygen Demand (BOD) and Total Suspended Solid (TSS) analysis.